Strategi Meningkatkan Minat Berwirausaha di Lingkungan Mahasiswa Masa Pandemi Covid-19 - Dewirahmadanirwati Dewirahmadanirwati (Jurnal Ilmiah Pendidikan Scholastic, 2020)
The problems underlying this problem are the high rate of unemployment and poverty that hit Indonesia, due to the Covid-19 pandemic, this has an impact on the difficulty of college graduates to find the desired job. And the low interest in entrepreneurship among students after graduating from college, due to a lack of self-confidence in entrepreneurship, causes the need for universities to change the mindset of students in order to become entrepreneurs. Strategies that can foster interest in entrepreneurship in students during the Covid-19 pandemic are changing the mindset of students from looking for work to creating jobs, explaining the advantages and advantages of becoming entrepreneurs, providing motivation and hone student business ideas, making business plans, making future targets and plans. forward, make financial reports, and explain the risks in business.